PENGARUH PENAMBAHAN TEPUNG BIJI LABU KUNING TERHADAP KEMATANGAN GONAD IKAN LELE SANGKURIANG (CLARIAS SP) - K Milla; Yulianus Linggi (Nusa Cendana University, 2018)
Abstract - Pumpkin seeds contain lots of vitamin E so it can be used as a supplement for the brood fish to improve the maturities gonad. This study used a pumpkin-seed flour added in to the feed (pellets) which aims to determine the index maturity of gonad (IMG) 0f lele sangkuriang (Clarias sp.), and the concentration of pumpkin-seed flour is effective against gonad maturity. The study was conducted for 2 months using completely randomized design (CRD) with the treatment of pumpkin seed concentration in the feed ie: 0, 100, 150 and 200 gram /kg of feed each treatment was repeated 3 times. The results shows that the highest IKG value was 5.7 (± 0.55) in treatment with 200 g / kg of feed compared with controls whose IGM value was only 2.6 (± 0.39), while treatment with 100 and 150 g / kg of feed obtained by IMG value 4,21 (± 0,89) and 44,98 (± 0,48). The data analysis, ANOVA, showed that the treatment hight significant (P˂ 0.01) on IMG.The study condution concluded that the addition of pumpkin-seed flour into the feed can increase the maturity of the gonad of lele sangkuriang. Keywords : Pumpkin Seeds, IKG, Catfish.